ROVI: a robot for visually impaired for collision- free navigation - Allan Melvin, A.; Prabu, B.; Nagarajan, R.; Bukhari, Illias (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.